Antifone Mariane : Testo, commento e musica - FALSINI, Rinaldo (Bonsai, 2009)
Premessa -- 5 -- Introduzione -- 7 -- Alma Redemptoris Mater -- 10 -- Ave Regina caelorum -- 18 -- Regina caeli -- 26 -- Salve Regina -- 34 -- Sub tuum praesidium -- 42 -- Inviolata -- 48 -- Ave Maria -- 54 -- Angelus Domini -- 60 - -